Material barriers, cultural boundaries: A mixed-methods analysis of gender and labour market segmentation in Bangladesh - Naila Kabeer; Lopita Huq; Muhammad Mahabub Rahaman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Data on female labour force participation in Bangladesh suggest that, despite the increase in female-intensive employment opportunities through microfinance, export garment manufacturing, and community-based services, the majority of working women are concentrated in home-based activities. There have been various attempts to explain this, with some focusing on economic explanations which stress women's education and skills, domestic responsibilities, and household wealth while others draw attention to cultural norms and practices organized around the male breadwinner ideology and purdah norms which require women to remain within the home. This paper combines data from a purposively designed survey of women from different districts of Bangladesh with in-depth interviews with a sample of these women to explore these different explanations. It finds that while women's capital endowments spell out the employment possibilities available to women, these intersect with cultural restrictions on women's behaviour, imposed as much by those around them as by their own values and beliefs. The result is the highly stratified market for female labour that we observe in the data.
Keywords: B54; J24; J42; 330; gender discrimination; labour market segmentation; mixed methods; cultural norms; South Asia